All‐Inorganic CsPbI2Br Perovskite Solar Cells: Recent Developments and Challenges. Issue 12 (20th October 2021) - Ullah, Saad; Wang, Jiaming; Yang, Peixin; Liu, Linlin; Li, Yuqiao; Yang, Shi-E.; Xia, Tianyu; Guo, Haizhong; Chen, Yongsheng
Abstract : In the past decade, organic–inorganic halide perovskites (OIHPs) perovskite solar cells (PSCs) have received gigantic research attention owing to their prompt development in power conversion efficiency (PCE) from the initial 3.8% for the first prototype in 2009 to the present state‐of‐the‐art value of 25.5%. However, due to the weak‐bonded organic components in the hybrid crystal structure, the intrinsic chemical instability of OIHPs persuaded by humidity, ultraviolet light, and heat remain a challenging issue for them to meet industrialization‐specific requirements. Parallel to the flourishing of OIHPs, the progress of inorganic cesium‐based metal halide PSCs (CsPbX3, X = I, Br, and mixed) is hastening with PCEs over 20%. Due to its excellent stability under thermal and high humidity conditions, CsPbI2 Br is one of the most fascinating inorganic perovskites and a notable research hotspot in the field of perovskite photovoltaics (PV). Herein, recent developments of CsPbI2 Br‐based PSCs including the optoelectronic properties, processing methods for preparing CsPbI2 Br films, stability of devices, and efficiency improvements are reviewed and deliberated. Finally, cutting‐edge engineering approaches for optimizing the PV performance are discussed and new challenges and perspectives for future research in this field are recognized. Abstract : Herein, recent developments of CsPbI2 Br‐based perovskite solar cells (PSCs) including the optoelectronic properties, processing methods for preparing CsPbI2 Br films, stability of devices, and efficiency improvements are reviewed and deliberated. Finally, cutting‐edge engineering approaches for optimizing the photovoltaic performance are discussed and new challenges and perspectives for future research in this field are recognized.